"Happiness is not my companion" : the life of General G.K. Warren - Jordan, David M., 1935- (Indiana University Press, 2001)
"Happiness Is Not My Companion"The Life of General G.K. WarrenDavid M. JordanThe valorous but troubled career of the Civil War general, best known for his quick action to defend Little Round Top and avert a Union defeat at Gettysburg. Gouverneur K. Warren, a brilliant student at West Point and a topographical engineer, earned early acclaim for his explorations of the Nebraska Territory and the Black Hills in the 1850s. With the start of the Civil War, Warren moved from teacher at West Point to.